Trading of Indonesian Crude Palm Oil Supply Chain and its Impact on Economic Growth: Implementation of Theory of Comparative Advantage and the Competitive Advantage of Nation - Maksum, Azhar; Muda, Iskandar; Lubis, Arifin; Azhar, Ibnu Austrindanney Sina (International Journal of Energy Economics and Policy, 2021)
The purpose of this study was to determine the effect of the volume and value of palm oil exports consisting of Crude Oil of Palm Kernel, Other Crude Oil of Palm Kernel, Solid fractions of refined palm kernel oil, Palm kernel olein, refined, bleached & deodorized (RBD) and Palm kernel oil bleached & deodorized against Economic Growth. This type of research is quantitative. The sample used is the development of Indonesian palm oil exports in the period 1970 to 2017. The analytical tool used is a structural approach which is completed with the WarpPLS Version 7.0 application. The results show that the export variables of Crude Oil of Palm Kernel, Other Crude Oil of Palm Kernel, Solid fractions of refined palm kernel oil, Palm kernel olein, refined, bleached & deodorized (RBD) and Palm kernel oil, RBD have an effect on Economic Growth. Novelti produced by this research shows that oil palm production makes a significant contribution to economic growth in a country and this supports and strengthens the theory of Theory of Comparative Advantage and Theory of Competitive Advantage. Keywords: Economic Growth, Crude Oil of Palm Kernel, Other Crude Oil of Palm Kernel, Solid fractions of refined palm kernel oil. JEL Classifications: Q11, Q21, Q41 DOI: https://doi.org/10.32479/ijeep.11766